Impact of infrastructure on trade, food security and economic growth in African countries - Yahaya, Auwal (2018)
In line with the theoretical and empirical discussions on the relevance of infrastructure to sustainable growth and development, the first objective of this study examined the impact of hard infrastructure facilities such as road, ICT and the soft infrastructure (documents per shipment to export/import, cost levied on 20 foot container and time necessary to export/import) on the export volume in the African countries. In the second objective, the study determined the impact of infrastructure- road, clean water and improved sanitation on food security in African countries. Whereas in the third objective, the impact of infrastructure (power, road, water & sanitation and ICT) on economic growth in African countries was assessed. Moreover, the study went further and assessed the indirect effect of infrastructure on economic growth through, health and education outcomes- life expectancy and mean years of schooling. The traditional panel methods of pooled OLS, fixed and random effect estimators are used in the first objective; while for the second and third objectives, the generalized method of moments (GMM) was employed. Giving the first objective, results showed a significant positive relationship between road infrastructure and export of the African countries, but not ICT. This may have to do with the nature of the products that generally dominate the African countries` exportprimary commodities that could still be produced even with less use of the ICT. On the soft infrastructure indicators, only number of documents and the cost per container for export are found to influence the region`s export, negatively; albeit only in the exporting countries. By implication, the provision of a well-developed infrastructure (hard and soft) might be a key to the successful accomplishment of the continent`s target of increasing its competitiveness and trade share in the global market. Findings in the second objective found that access to sanitation due improve food insecurity, but not water and road infrastructure. Based on the present specifications, no significant relation between access to water and the dependent variables was found. On the positive coefficient found for the road infrastructure, it could be said that the road infrastructure indicator used may not have suited the true picture of the common mode of commuting in the rural and sub-urban centers across the continent- footpaths. Thus, other than the traditional notion of increasing the domestic food production, access to better infrastructure (water & sanitation) can help reduce the high prevalence of food insecurity across the African countries. In the third objective, a positive and significant relationship between infrastructurepower, road, water & sanitation and ICT and economic growth in the countries is obtained. Further investigations also revealed that the infrastructure variables positively impact on economic growth of the African countries, through the channels of health and education outcomes. It has hence confirmed on the existence of a positive link between infrastructure access and achieving health and education outcomes; and also, that health and education outcomes do improve economic growth of nations. Impliedly, the current findings highlighted on some sort of complementarity between building of better infrastructure for achieving economic growth and policies meant to improve life expectancy and mean years of schooling. Similarly, ensuring the provision of a better road access that will link rural and urban settlements could save the government from building of more health or education outlets across the countries. For policy implication, the study suggest for the need of more efforts from both the regional and national governments in Africa to ensure people get access to basic infrastructure services in order to achieve an inclusive economic growth in the region.